Application of Three Dimensional Geometric Morphometric Analysis for Sexual Dimorphism of Human Skull: A Systematic Review - Ibrahim, Abdelnasser; Alias, Aspalilah; Shafie, Mohamed Swarhib; Nor, Faridah Mohd (IIUM Medical Journal Malaysia, 2019)
The present systematic review explores the most sexually dimorphic parameters by using geometric morphometric analysis of human skull. An extended search was conducted in Google Scholars and PubMed (published between 2005 and 2017). The main inclusion criteria were research articles published in English, and studies that used geometric morphometric analysis for classification of human skull. The literature search identified 54 potential relevant articles whereby, five had met the inclusion criteria. Most studies reported positive contribution of geometric morphometric as an alternative and accurate tool for classification of unknown human crania. Geometric morphometric method resulted in a high classification accuracy of sexual dimorphism among different populations. Further studies are required to approach the best method used for varied types of postcranial bones equipped with a more advanced meta-analysis of the results.